Gut Microbiota-Mediated NLRP12 Expression Drives the Attenuation of Dextran Sulphate Sodium-Induced Ulcerative Colitis by Qingchang Wenzhong Decoction. (2nd April 2019) - Sun, Zhongmei; Pei, Wenjing; Guo, Yi; Wang, Zhibin; Shi, Rui; Chen, Xiaowei; Zhao, Xingjie; Chen, Chen; Liu, Jiali; Tan, Xiang; Yuan, Wenjing; Mao, Tangyou
Abstract : Qingchang Wenzhong Decoction (QCWZD) is a newly developed, effective traditional Chinese herbal formulation for ulcerative colitis (UC). In earlier studies, we found that QCWZD could relieve the clinical symptoms of UC patients, reduce inflammation, and improve the intestinal barrier function in dextran sulphate sodium (DSS)-induced UC rats. However, the relationship between QCWZD and the gut microbiota in colitis was not clarified. In this study, we established a rat model of DSS-induced UC and then investigated the regulatory effects of QCWZD on the gut microbiota using 16S rRNA analysis. We also determined the expression of NLRP12 after QCWZD administration. Our findings suggested that QCWZD administration could modulate gut microbiota composition and selectively promote the protective strains such as Butyricimonas, Blautia, and Odoribacter, whereas the enteric pathogens including Clostridium and Dorea were significantly reduced after QCWZD treatment. It is noteworthy that QCWZD administration was identified to promote gut microbiota-mediated NLRP12 expression by inhibiting the activity of the TLR4/Blimp-1 axis. In conclusion, our study supports the potential of QCWZD administration as a beneficial therapeutic strategy for UC.